Kepastian Hukum Kredit Online - Pradini, Devy Iziana; Hariyadi, Izzi Zya; Khoir, Shohibul (Universitas Negeri Malang, 2020)
This paper aims to discuss the validity of a contract in online credit and the provision of collateral for online credit as an embodiment of the 5C principle in banking. The method of study uses a normative juridical approach to the legislation and conceptual approach. Online credit contracts are legally valid because they meet the legal requirements of a contract, only the legal certainty is low because the parties do not know firsthand the good intentions of the parties. The provision of collateral in online credit is not against the law, it’s just that the precautionary principle that the bank should apply in providing credit is not fulfilled. The creditor does not have a guarantee for the debtor’s debt repayment if at any time the debtor is unable to repay the loan or break the promise.